Case Report: A Functional Approach to Deal With Sexual Harassment Within Families - Meiling, Li; Hania, Alishba; Waqas, Muhammad (Frontiers in Psychology, 2022)
The family represents for the child, the universe of his existence, and the parents, the family are the stability poles of this universe. When the family environment, rather than being one of comfort and safety becomes a place of deprivation, pain and violence, the child is the one who will suffer the most. Present work provides practical suggestions to enable a person to become happy, balanced and efficient adult. A.A was a 16 years old girl who was self-referred to the psychologist with complaints of getting sexually harassed by brother in-law, difficulty in maintaining academic challenges, communication gap with parents, fear of getting harassed again and difficulty in handling own anger since last 7 years. The assessment modalities used with the client are Behavioral Observation, Clinical Interview, Baseline Charts, School Children Problem Scale [SCPS] to rule out emotional behavioral problems, Adult Child Interaction Test [ACIT], and Downward Arrow Technique for cognitive assessment. The management plan was based on Self-protection awareness from harassment, reduce fear and unexplained emotions of grief, increasing self-esteem, to design a proper schedule for studies and develop good communication ability. Post assessment showed Anger reduction to 40%, Communication gap with parents reduced to 50%, Fear of harassment reduced to 40% and Self-image improved up to 40%. Sessions were based on 9 meetings.